Medikamentöse Therapie des Ovarialkarzinoms in der Primär- und Rezidivsituation = Pharmaceutical treatment of ovarian cancer in primary and recurrent situations - Marmé, Frederik; Harter, Philipp; Ataseven, Beyhan (Der Onkologe, 2019)
BackgroundThe understanding of the molecular basis and heterogeneous nature of the tumor biology of ovarian cancer has rapidly increased over the last 10 years. In addition to the introduction of antiangiogenesis as a treatment principle this has also led to the definition of a central treatment target. Defects in homologous recombination are therapeutically usable based on the principle of synthetic lethality and have led to the introduction of PARP inhibitors as an integral component of treatment.Material and methodsThis review is based on a selective literature search of the PubMed database, relevant meeting abstracts and current national as well as international guidelines.ResultsBased on the introduction of PARP inhibitors in addition to antiangiogenic therapies, the treatment options for ovarian cancer have become more refined and diversified. The PARP inhibitors as maintenance treatment define a new standard in the primary treatment of BRCA-mutated advanced ovarian cancer. The BRCA mutation status provides indispensable information for individual treatment selection at the beginning of the first-line therapy also with respect to the sequence of treatment. In addition, the strictly defined classification into platinum sensitivity and resistant recurrences based exclusively on the platinum-free interval was recently abandoned. Instead, the importance of multiple factors that need to be considered in the decision whether a platinum-based treatment would be a good option for an individual patient was emphasized. The respective treatment options and their evidence are discussed separately for the first-line and recurrent settings as well as for the different treatment principles.DiscussionThe integration of effective targeted therapies has for the first time led to different treatment choices in a specific clinical situation. Clinical development in large phase III trials has picked up pace, currently focusing mainly on immunotherapies and their integration into the current treatment strategies including chemotherapy, bevacizumab and PARP inhibitors.
Gesehen am 27.03.2019